PUSAT PELATIHAN NASIONAL OLAHRAGA BILIAR DENGAN KONSEP ARSITEKTUR MODERN DI SETIABUDI, JAKARTA SELATAN - Rizky Suryandri Devi; Harfa Iskandaria; Putri Suryandari (MAESTRO, 2021)
The billiard sports national training center is a place that accommodates a type of activity that provides special training to billiard athletes, both general athletes and national teams from all over Indonesia. Not only special training for athletes, general special training can also be done as a form of socialization for the sport of billiards because of the large number of enthusiasts for this type of sport. For the design of the Billiard Sports National Training Center in Setiabudi, South Jakarta, it will use a modern architectural concept because building a sports center itself does not require a lot of ornamental designs. The interior and exterior design of the building emphasizes simplicity and uniformity so that it is efficient with needs and functions.